KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH PERFORMANCE PADA MAN 1 DAN 2 DI AMUNTAI KABUPATEN HULU SUNGAI UTARA - Chairul Echwan (Cross-border, 2021)
This research started from the writer's curiosity about the transformational leadership of madrasah principals performance at MAN 1 and 2 in Amuntai, Hulu Sungai Utara Regency. This type of research is a qualitative research using descriptive method. The data collection procedure in this study used observation, interviews and documentation. The results of this study indicate that the transformational leadership that takes place at the Head of MAN 1 and 2 in Amuntai can be seen from the ability of the Head of Madrasah to be a charismatic leader, able to demonstrate commitment to the goals of the madrasa, able to act as an enthusiastic motivator, and always exploring new ideas and solutions creativity of teachers and employees. Madrasah principals also always encourage teachers and employees to learn and practice new approaches, pay attention to needs and involve teachers and employees in decision making.